Practicing greatness : 7 disciplines of extraordinary spiritual leaders - McNeal, Reggie; Leadership Network (Dallas, Tex.) (USA Jossey Bass, 2006)
Based on his experience coaching and mentoring of Christian leaders across a wide variety of settings, leadership expert and consultant Reggie McNeal shows spiritual leaders how to move from being simply good enough to being great by living seven essential disciplines: self-awareness, management of emotions and expectations, a lifelong commitment to learning, a sense of mission, the ability to make great decisions, the commitment to be in community, and the intentional practice of solitude and contemplation. --From publisher's description.
The discipline of self-awareness -- The discipline of self-management -- The discipline of self-development -- The discipline of mission -- The discipline of decision making -- The discipline of belonging -- The discipline of aloneness.
"Leadership Network publication."
Includes bibliographical references and index.
Keywords: Christian leadership; Leadership -- Religious aspects -- Christianity